Revision of Lutnes Cameron (Hymenoptera: Eupelmidae) - Gibson, Gary A. P. (Zootaxa, 2018)
Argaleostatus Gibson, 1995 is synonymized under Lutnes Cameron, 1884 (Hymenoptera: Chalcidoidea: Eupelmidae: Eupelminae) n. syn. and its type species, Eupelmus testaceus Cameron, 1884, is transferred to Lutnes as L. testaceus (Cameron) n. comb. The species of Lutnes are revised and six species are recognized, including the type species, Lutnes ornaticornis Cameron, 1884, plus L. testaceus, L. biguttatus (Girault, 1913), and three new species, L. aurantimacula Gibson n. sp. (Ecuador), L. infucatus Gibson n. sp. (Ecuador), and L. afrotropicus Gibson n. sp. (Cameroon). The first five species are based on females from the Neotropical region, whereas the last species is based on a female from Cameroon. This Afrotropical record is the first for the genus outside of the Neotropical region. Males are unrecognized for the genus. Monophyly and relationships of the genus are discussed and the species are keyed and illustrated through macrophotography.